2005
DOI: 10.1109/tns.2005.852748
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of heavily irradiated silicon pixel sensors and comparison with test beam measurements

Abstract: Abstract-Charge collection measurements performed on heavily irradiated p-spray DOFZ pixel sensors with a grazing angle hadron beam provide a sensitive determination of the electric field within the detectors. The data are compared with a complete charge transport simulation of the sensor which includes free carrier trapping and charge induction effects. A linearly varying electric field based upon the standard picture of a constant typeinverted effective doping density is inconsistent with the data. A two-tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 18 publications
0
57
0
Order By: Relevance
“…It is clear that the simulation can accommodate the expected leakage current which is smaller than the measured current by a factor of three. The same choice of parameters can also account for the observed rate of signal trapping [2].…”
Section: Model Tuning and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that the simulation can accommodate the expected leakage current which is smaller than the measured current by a factor of three. The same choice of parameters can also account for the observed rate of signal trapping [2].…”
Section: Model Tuning and Resultsmentioning
confidence: 99%
“…A more detailed description of the double junction model and its implementation can be found in Ref. [2].…”
Section: Sensor Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…At F ¼ 6 Â 10 14 n eq =cm 2 the cross section ratio 1 The comparison of the measured and simulated profiles at F ¼ 6 Â 10 14 n eq =cm 2 can be found in Ref. [2].…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [2] we have proved that this picture does not provide a good description of irradiated silicon pixel sensors. In addition, it was shown that it is possible to adequately describe the charge collection characteristics of a heavily irradiated silicon detector in terms of a tuned double junction model which produces a double peak electric field profile across the sensor.…”
Section: Introductionmentioning
confidence: 98%